Adverse events following the first dose of ChAdOx1 nCoV-19 (COVISHIELD) vaccine in the first phase of vaccine roll out in Nepal - Shrestha, Shrijana; Devbhandari, Ranjan Prasad; Shrestha, Ashis; Aryal, Sushant; Rajbhandari, Piyush; Shakya, Binnam; Pandey, Prabesh; Shrestha, Ram Krishna; Gupta, Mayuri; Regmi, Archana (Journal of Patan Academy of Health Sciences, 2021)
Introduction: Nepal started the first phase of COVID-19 vaccination for frontline healthcare workers in January 2021 with the ChAdOx1 nCoV-19 (COVISHIELD) vaccine. We conducted active surveillance of Adverse Effect Following Immunization (AEFI) after the first dose of the vaccine administered at one of the sentinel sites for vaccination, Patan Academy of Health Sciences (PAHS).Method:  All the 5591 first dose ‘COVISHIELD’ vaccine recipients between 27 Jan -5 Feb 2021 at PAHS, were approached through phone calls to collect data on AEFI.  Incidence of common AEFIs in different age groups, gender and those with previous history of COVID-19 were analyzed. Presence of any Adverse Events of Special Interest (AESI) were evaluated.Result: Out of 5591 vaccines recipient, 3991 (71.3%) responded to the phone call and AEFI was noted in 3394 (85.04%) of them. Minor AEFI was seen in 3391 (84.9%), severe Minor AEFI in 1 (0.02%) and Serious AEFI in 2 (0.05%). Out of 807 vaccine recipients with previous history of COVID-19, 709 (87.9%) had AEFI while of the 3184 with no past history of COVID-19, 2685 (84.3%) had AEFI. However, some of the systemic AEFIs were noted more frequently in those with past COVID-19 infection. A total of 1886 (55.6%) took self-medication for symptom relief, 278 (8.2%) took leave from work while 26 (0.76%) visited health facility for the AEFIs.Conclusion:  Most AEFIs following the first dose of COVISHIELD vaccine were mild and resolved within a few days. Except for one case of anaphylaxis, no other AESI were encountered.